Analysis of Employee Performance in The Department of Education and Culture, Lubuklinggau City - Riwukore, Jefirstson Richset; Susanto, Yohanes; Pilkandis, Jekki; Habaora, Fellyanus (AIBPM Publisher, 2021)
The aims of this research are to determine the impact of incentivizing, motivation and discipline on the performance of The Department of Education and Culture of Lubuklinggau City employees simultaneously and partially. Qualitative method was used in this research, with 57 employees at The Department of Education and Culture of Lubuklinggau City as a sample. Multiple linear regression test, coefficient of determination test, f-test and t-test were used in this research as data analysis technique. The results obtained from partial test (t-test) proved that incentivization, motivation, and discipline each had a partially significant impact on employee performance at the office of The Department of Education and Culture of Lubuklinggau City where t (count) > t (table) and also sig 0,001 < 0,05. Incentives, Motivation, and Disciplines have simultaneously significant impact on employee performance, where t (count) > t (table) and also sig is 0,000 < 0,05. This research is an important contribution to the regulation of human resources in The Department of Education and Culture of Lubuklinggau City so. The determination of discipline, incentives, and motivation tends to be neglected in improving performance so that it is necessary to examine the relationship to performance in human resources, which is an important contribution of research.